Alginate-based composite materials for wound dressing application:A mini review - Varaprasad, Kokkarachedu; Jayaramudu, Tippabattini; Kanikireddy, Vimala; Toro, Claudio; Sadiku, Emmanuel Rotimi (Carbohydrate polymers, 2020)
[Display omitted] •This review aims to present the importance of sodium alginate-based materials in wound dressing applications.•Presently available forms of the alginate-based biomaterials are discussed.•Future perspectives are suggested, based on the topic’s relevance. Alginate biopolymer has been used in the design and development of several wound dressing materials in order to improve the efficiency of wound healing. Mainly, alginate improves the hydrophilic nature of wound dressing materials in order to create the required moist wound environment, remove wound exudate and increase the speed of skin recovery of the wound. In addition, alginate can easily cross-link with other organic and inorganic materials and they can promote wound healing in clinical applications. This review article addresses the importance of alginates and the roles of derivative polymeric materials in wound dressing biomaterials. Additionally, studies on recent alginate-based wound dressing materials are discussed.